The Economics of Tobacco Taxation and Employment in Indonesia - World Bank Group (World Bank, Washington, DC, 2017)
The objective of this report is to analyze the recent employment trends in the Indonesian tobacco industry and estimate the potential effects of raising cigarette taxes on employment in the tobacco manufacturing sector. The report provides new evidence to contribute to the ongoing debate about the effects of raising cigarette taxes on tobacco sector employment. It complements the current analytical work conducted by the World Bank, in partnership with the American Cancer Society, to explore the employment conditions and livelihoods of tobacco and clove farmers and kretek rollers in Indonesia. This report is structured as follows: section one gives introduction. Section two provides a review of the global evidence on the impacts of raising cigarette taxes on population health outcomes and on the economy. Section three presents an overview of the cigarette tax reforms in Indonesia in recent years and discusses the government of Indonesia’s plans for reforming the cigarette tax structure. Section four discusses the employment trends in the tobacco industry in Indonesia, analyzes workers’ characteristics and compares workers to similar sectors and socio-demographic profiles. The section also discusses the potential impacts of raising cigarette taxes on employment by presenting results of simulations. The final section five, discusses the results in light of the current debate over cigarette tax reform in Indonesia and provides policy recommendations on the employment aspects of the reform.